The Antibacterial Activity of Natural Product Black Tea Theaflavins On Streptococcus Mutans. (October 2019) - Chen, Zhenyi; Wang, Yina; Guo, Chengyu; Li, Hong
Abstract: Objective The aim of the study is to investigate the antibacterial effect of the black tea theaflavins (TFs) on Streptococcus mutans (S. mutans) which cause the dentin caries. Methods (1) Broth dilution method was used for the determination of minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). (2) Mixed bacterial suspension with three different concentrations of TFs and recorded pH values before and after anaerobic incubation. (3) Scanning electron microscopy was used for observing bacteria morphology. Results (1) The MIC and MBC were 0.5mg/ml and 1.0mg/ml respectively. (2) With the increasing concentration of TFs, the ability of bacteria to produce acid gradually decreased. (3) TFs changed the shape of S. mutans. Conclusions Theaflavins inhibits S. mutans effectively.